SISTEM STANDARISASI MODULAR BAGI PERMUKIMAN SEBAGAI SARANA PERBAIKAN LINGKUNGAN DI DAERAH TRANSFORMASI RURAL-URBAN - Priaji Martana, Salmon (Jurnal Natah; Vol. 3, No. 1 Februari 2005)
Urbanization by means of the infiltration of urban functions into rural area has caused many problems. In human settlement sector, low quality houses emerged on rural-urban transformation area, without any concern on safety, comfort and health factors as well as any other living standards. The main cause was probably a cultural shock, the lack of education and environmentally awareness, but things have been worse since no access can be build for the community to the help of professional environment designer. As a result, the settlement is growing without any proper direction, generated merely by economic aspect producing new slum enclaves. Several ways are suggested to solve this problem, one of them is by establishing modular standard in housing. For the last several years many building codes and standards have been built. Unfortunately, those standards are too general or even too sophisticated, only limited number of people could understand. Standard system described in this article is a ‘down to earth’ modular housing standard for people from any kind of background. Simple people without any building knowledge could benefit from it. The implementation would not need any special skilled laborer while still maintain to meet the minimum standard for safety, comfort and health aspects. Modular standard also provide an opportunities for small scale construction industries, thus open a new field of work among the community. This standard is also eliminating the difficulties on people’s access to the assist of professional environment designer, in this case architect.
Keywords: standardization, modular coordination.